The 150 most important questions in cancer research and clinical oncology series: questions 6–14: Edited by Chinese Journal of Cancer (Chin J Cancer, 2017)
To accelerate our endeavors to overcome cancer, Chinese Journal of Cancer has launched a program of publishing 150 most important questions in cancer research and clinical oncology. In this article, nine more questions are presented as followed. Question 6. Why do nasopharyngeal carcinomas rarely metastasize to the brain? Question 7. Can distant spread of cancer cells be blocked by inhibiting the remodeling of high endothelial venules in the sentinel lymph node? Question 8. What sort of live-imaging techniques can be developed to directly observe the dynamic processes of metastasis? Question 9. How does chronic hepatitis prevent liver metastasis from colorectal cancer? Question 10. How many types of host cells contribute to forming the pre-metastatic niche in the lung favorable for metastasis? Question 11. Why do cancers rarely metastasize to the small bowel? Question 12. Why do glioblastomas rarely metastasize outside the central nervous system? Question 13. Despite increased understanding of the molecular genetic events leading to the development and progression of high-grade gliomas, these tumors are the most therapeutically refractory among all human cancers. What then would be the most effective therapeutic approaches to treat what in essence can be regarded as a whole brain malignancy, since even a surgical resection of greater than 99% of tumor tissues is invariably associated with recurrence? Question 14. The blood–brain barrier (BBB) effectively limits a wide variety of potential therapeutic agents from reaching glioma cells widely dispersed in the brain. What therapeutic approaches can be used to breach the BBB and allow therapeutic agents to seek out and kill these tumor cells?